Health promotion and political culture: reconstructing the consensus - Stotz, Eduardo Navarro; Araujo, José Wellington Gomes (Saúde e Sociedade, 2004)
An evaluation about health promotion and empowerment is presented in this paper. Fundamental principles of a public health culture are studied from a problem-posing point of view, as they are the base of public policy proposals specially formulated for the so called "developing" countries. Empowerment is particularly analyzed, since it is considered a way chosen for individual and collective (community, social) health promotion, connected to social groups under more vulnerable social conditions. The Welfare State crisis and the neoliberal approach, applied during the eighties to overcome it, gave grounds to examine this proposal, focusing on the changes occurred to capitalism in terms of conceptual and moral introjection of reality, particularly when it concerns social policies based, in the principle of equity in oposition to that of universality. The World Health Organization adopted this principle, integrating hence the dominant culture to the health sector yet, not much reflective, strongly technicist and normative. Building up a new culture, capable of admitting the role of common knowledge, incorporating the experience of civil society, backing up the struggles for recognition of the citizens' health rights and demanding the right to health as a universal right are challenges posed by the authors.